Resilient or fragile? modelling economic disruptions in India's electronics sector due to the Red Sea crisis - Sarkar, Bishal Dey; Gupta, Laxmi; Jagtap, Sandeep (Elsevier, 2025)
The Red Sea crisis and the recent attacks on commercial ships have drawn significant attention worldwide, underscoring the need to understand how such geopolitical conflicts can disrupt global supply chains and economic stability. This paper thoroughly examines the complex impacts of the crisis on India's electronics and photonics sector, recognizing the sector's crucial importance as a fundamental pillar in the country's economic structure. The study creates a mathematical model to assess how disruptions in the Electronics and Photonics Sector affect India's economy in light of the Red Sea Crisis. The model uses two specific methods: interval programming and input-output modelling. How disruption in one area of the economy ripples to another is studied using Wassily Leontief's Inoperability Input-output Model (IIM). IIM now includes interval programming to handle data uncertainties. The findings disclose that, because of the Red Sea crisis, Indian Sector has experienced a huge economic loss of 605.52 million USD. The study also determines which sectors are anticipated to suffer significant losses due to the crisis, allowing decision-makers to prioritize their investment plans. Further, the research uses the inoperability value to analyse the interconnections between the sectors. Additionally, a decision-support conclusion is included in the research to analyse the sectors under various situations.
Keywords: Economy loss; Interoperability; Interval programming; Input-output modelling; Red Sea crisis; Electronics and photonics sector; 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; Generic health relevance; Logistics & Transportation; 3304 Urban and regional planning; 4406 Human geography